Pendampingan Majelis Ta’lim dalam Meningkatkan Pengamalan Keagamaan di Desa Kesugihan Kecamatan Pulung Kabupaten Ponorogo - Yoga Novian Prasetyo; Diyan Putri Ayu (Social Science Academic, 2023)
Learning does not require age and there is no limit, both children and parents are allowed to study. The scope of majlis ta'lim is a place to gather and study for people who want to explore the teachings of IslamThis research is a qualitative research, namely a contextual research that uses humans as instruments, and is adjusted to a reasonable situation in relation to data collection which is generally qualitative in nature. This study uses a communication approach that is connected with theories that are considered related to the object of research, then used to obtain general conclusions about the da'wah strategies used by the taklim assembly. The results of the research and the conclusions from this article are the efforts of the Baiturahman ta'lim assembly in improving religious practice prayer services in Kesugihan Village, namely by fostering the soul and spiritual mentality of the congregation of the Baiturahman ta'lim assembly so that many of them are increasingly obedient in worship